#### Answer

$3n+6$

#### Work Step by Step

$n$ = the first even integer
$n+2$ = the second even integer
$n+4$ = the third even integer
Thus the sum is:
$n+(n+2)+(n+4)=3n+6$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$3n+6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.